Implementation Of The Community Empowerment Model For Village Owned Enterprises (Bumdes) Batokan Kasiman Bojonegoro - Agustin, Imma Widyawati; Nur Shochibul Asror; Dimas Wisnu Adrianto (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2025)
A key strategy for addressing the issues of poverty and limited access to social and economic resources is community empowerment. Village-Owned Enterprises is one approach that can be utilized to improve community groups (BUMDes). Subjective approaches are used in the research to collect data through meetings, perceptions, and examination of relevant reports. Institutional analysis, Venn diagram, SWOT analysis, and project analysis are the analyses that are employed. The study's findings demonstrate that enhancing community welfare has resulted from the application of the BUMDes model for community group strengthening in Batokan Sejahtera Village. In addition, BUMDes offers community training and support in the areas of product marketing, financial management, and business management. Nevertheless, there are still a number of obstacles in the way of using BUMDes to implement the community empowerment paradigm. These difficulties include a lack of availability to financing for businesses, a small market for the goods produced, and a lack of awareness among the general public of the significance of BUMDes for economic empowerment. Local governments must help BUMDes become more sustainable and successful by creating market access, offering business funding, and offering mentoring and training. In addition, BUMDes and associated stakeholders including farmer associations, for-profit businesses, and other business actors must work together.